Plant characteristics drive ontogenetic changes in herbivory damage in a temperate forest. (15th September 2022) - Kurokawa, Hiroko; Oguro, Michio; Takayanagi, Sakino; Aiba, Masahiro; Shibata, Rei; Mimura, Makiko; Yoshimaru, Hiroshi; Nakashizuka, Tohru
Abstract: Understanding ontogenetic differences in plant defenses and herbivory damage is crucial for obtaining a better understanding of plant life‐history strategies, community assembly, and dynamics. Although many studies have compared plant defenses or herbivory damage between ontogenetic stages (e.g. sapling vs. adult), how the effects of plant characteristics on leaf herbivory damage change during plant ontogeny has rarely been examined across species or in a species‐rich natural community. To elucidate the effects of plant characteristics, we compared the relationships of leaf herbivory by insects with stem density, plant size, and leaf traits between saplings and adults for almost all co‐occurring woody species (56 species, ranging from rare to abundant) in a Japanese temperate forest. In most species, adults were larger, fewer in number, and had leaf traits that were potentially less favorable to herbivores (e.g. stronger, or with more phenolics). In contrast, we observed species‐specific directions of changes in herbivory damage between adults and saplings with plant phylogeny or density having no clear effect. The relationships between some plant traits and herbivory damage were ontogeny dependent, indicating a shift from chemical to physical defense as plants mature, although most of the species characteristics studied were highly correlated between stages. Such ontogeny‐dependent relationships between plant traits and herbivory damage could cause variation in the ontogenetic changes in herbivory damage among species depending on the value of plant traits. Moreover, the direction and magnitude of the effects of ontogenetic differences in species traits on the ontogenetic differences in herbivory damage varied depending on the traits. Together, these factors could have caused the observed ontogenetic changes in herbivory damage among species. Synthesis. Our study demonstrated how relationships between plant characteristics and herbivory damage can change ontogenetically across many coexisting woody species in a forest community, suggesting that plant traits may perform different functions related to herbivory at different ontogenetic stages. This has rarely been considered in previous dualistic comparisons of individual traits and herbivory damage between ontogenetic stages, and it is vital for understanding plant life‐history strategies across stages in relationships with herbivores in natural communities. Abstract : Our study demonstrated how relationships between plant characteristics and herbivory damage can change ontogenetically across 56 coexisting woody species in a forest community, suggesting that plant traits may perform different functions related to herbivory at different ontogenetic stages. This has rarely been considered in previous dualistic comparisons of individual traits and herbivory damage between ontogenetic stages, and it is vital for understanding plant life‐history strategies across stages in relationships with herbivores in natural communities. 要旨: 植物の成長にともなう被食防衛と葉の食害率の変化を理解することは、植物の生活史戦略や群集の形成・動態を理解するために極めて重要である。これまで多くの研究が、稚樹や成木といった成長段階の間で被食防衛や食害率を比較してきたが、食害率と被食防衛との関係が植物の成長にともなってどのように変化するかは、多種で構成される自然生態系ではほとんど調べられてこなかった。 被食防衛戦略における植物特性の影響を明らかにするため、日本の温帯林に位置する小川試験地（北茨城市）に共存するほぼ全ての木本種（レア種から優占種までを含む56種）を対象に、昆虫による葉の食害率と単位面積あたりの幹本数（アバンダンス）、植物個体サイズ、葉の形質との関係を稚樹と成木で比較した。 群集全体でみると、ほとんどの種で成木は稚樹より個体サイズが大きく、幹本数が少なかった。また、成木はより硬く、より多くのフェノール性物質を持つなど、植食者にとって好ましくない形質の葉を持っていた。一方、成長にともなう食害率の変化の方向性は種ごとに異なり、植物の系統やアバンダンスはその方向性に明確な影響を与えていなかった。調査した植物特性のほとんどは成木・稚樹間で強く相関していたにもかかわらず、いくつかの葉形質と食害率との関係は稚樹と成木で異なり、植物が成長するにつれ化学的防衛から物理的防衛へと戦略が変化する可能性が示された。また、成長段階によって葉形質と食害率との関係が異なることは、成長にともなう食害率の変化が葉形質の種間差にも依存する可能性を示唆している。さらに、成木・稚樹間の葉形質の変化が成木・稚樹間の食害率の違いに及ぼす影響の方向性や大きさは、形質によって異なることがわかった。これらの要因により、成長にともなう食害率の変化の方向性に群集全体では一貫性が見られなかった可能性がある。 本研究では、共存する多くの木本種間で、葉形質と食害率との関係が植物の成長にともなって変化しうることを示した。つまり、同じ葉形質でも成長段階によって植食者に対する機能が異なる可能性がある。形質と食害率それぞれを成長段階間で比較した先行研究では、この可能性はほとんど考慮されてこなかったが、成長にともなう形質の機能の変化は野外における植物の生活史戦略を理解する上で極めて重要である。